PERFORMANCE OF BROILER PHASE FINISHER WITH VARIOUS LEVEL MAGGOT (Black Soldier Fly) ON STARTER PHASE - Wulandari, Eudia Christina; Nurdianto, Mohammad; Purwadi, Purwadi (Tropical Animal Science, 2022)
Broiler chickens are purebred chickens that have the ability to grow and develop quickly and produce meat in a short time (1-2 months) if kept intensively. Broiler chickens have a very important role as a source of animal protein derived from livestock. This study aims to determine how much influence the use of maggot flour in the ration has on the performance of broilers in the finisher phase after giving various levels of maggot in the starter phase. The material used in the study was broiler chickens aged 1-25 days using the Superchik Strain as many as 40 chickens sourced from each treatment and each replication as many as 2 tails. In this study, the feed ingredients used were commercial feed and maggot flour purchased from maggot breeders. The equipment used in the study was a cage made of husks that had been sanitized and equipped with a feeder, drinking container, gasloec, buckets, digital scales, plastic curtains, measuring cups, thermometers, and stationery. Using Completely Randomized Design (CRD) with 4 treatments, 5 replications for each replication of 2 tails. The results showed that the use of maggot level in the starter phase had a significant effect (P>0.05) on ration consumption (208.85a (T0); 185.32b (T1); 204.60ab (T2); 209.40a (T3). ) and had no significant effect (P<0.05) on body weight gain (907.1 (T0); 858.978 (T1); 895.3 (T2); 878.44)), feed conversion ratio (2.774 (T0) 2,627 (T1); 2,726(T2); 2,779(T3)), and drinking water consumption (442.13 (T0); 437.6 (T1); 453.87 (T2); 469.33 (T3)) . The ration consumption in treatment T0 was not significantly different from treatment T3 and treatment at T2. But the T2 treatment was not significantly different from the T1 treatment.